Evasion strategies of porcine reproductive and respiratory syndrome virus - Chen, Xin-xin; Qiao, Songlin; Li, Rui; Wang, Jing; Li, Xuewu; Zhang, Gaiping (Frontiers in Microbiology, 2023)
During the co-evolution of viruses and their hosts, viruses have developed various strategies for overcoming host immunological defenses so that they can proliferate efficiently. Porcine reproductive and respiratory syndrome virus (PRRSV), a significant virus to the swine industry across the world, typically establishes prolonged infection via diverse and complicated mechanisms, which is one of the biggest obstacles for controlling the associated disease, porcine reproductive and respiratory syndrome (PRRS). In this review, we summarize the latest research on how PRRSV circumvents host antiviral responses from both the innate and adaptive immune systems and how this virus utilizes other evasion mechanisms, such as the manipulation of host apoptosis and microRNA. A thorough understanding of the exact mechanisms of PRRSV immune evasion will help with the development of novel antiviral strategies against PRRSV.